Towards a Non-formal and Contextualized Environmental Education Process in the Community of Chacarita, Puntarenas, Costa Rica - Carvajal Oses, Milagro (2023)
Actions in coastal environmental education are scarce. Worldwide, numerous communities surrounding mangroves live in poverty. Costa Rica does not represent an exception to the above due to poor management and little empowerment of the communities towards natural resources. Thus, this article aims to demonstrate, from an educational model based on competencies, the first construction phases of a non-formal educational process in environmental matters developed in the coastal community of Chacarita, Puntarenas, Costa Rica. The researchers contextualized this educational project; therefore, they collected biological results of mollusks of commercial interest and mangroves for a year. Moreover, they carried out bird and mammal sightings and collected information on fishing in the area. Finally, they applied a survey to evaluate the knowledge and dispositions of the community. The results allowed the construction of educational materials and the development of skills. In addition, they showed that people from Chacarita are willing to receive environmental education as well as participate in activities such as cleaning and reforestation.